On the road to integration? Immigrant's demand for informal (& formal) education - Nicola D. Coniglio; Rezart Hoxhaj; Hubert Jayet (Global Labor Organization (GLO), 2019)
In this paper we study the allocation of time devoted to informal learning and education, i.e. those activities carried out during leisure time and outside formal education courses which boost individuals' human and social capital. For immigrants the private investment in these activities is likely to have relevant external effects as informal learning and education enhances the likelihood of greater socio-economic integration in the host society. We first develop a simple theoretical framework, which allows us to highlight the different constrains/opportunity costs faced by immigrants as compared with natives. Then, we empirically investigate the determinants of participation in informal education using the American Time Use Data (ATUS; period 2003-2015) which contains detailed information on daily time budgets of a large sample of immigrants and natives in the US. Consistently with a theoretical model of time allocation we find evidence that immigrants are more likely to engage in informal education and, conditionally on participation, they allocate more time to these activities. Over time, immigrants show a higher degree of assimilation into the host society. Our results also highlight heterogeneous patterns across gender.
Keywords: J15; J22; I20; 330; immigrants; time use; education; human capital